Effects of Tai-Chi Chuan Practice on Patterns and Stability of Lower Limb Inter-Joint Coordination During Obstructed Gait in the Elderly - Kuo, Chien-Chung; Chen, Sheng-Chang; Wang, Jr-Yi; Ho, Tsung-Jung; Lin, Jaung-Geng; Lu, Tung-Wu (Frontiers in Bioengineering and Biotechnology, 2021)
Losing balance or tripping during obstacle-crossing is one of the most frequent causes of falls in the elderly. As a low speed, low impact exercise, Tai Chi Chuan (TCC) can be promising in helping the elderly develop strategies for improved balance, inter-joint coordination, and end-point control during obstacle-crossing. This study investigates the effects of TCC training on the patterns and variability of the lower-limb inter-joint coordination during obstacle-crossing in the elderly. Fifteen older TCC practitioners and 15 healthy controls crossed obstacles of three different heights, while sagittal angles (x) and angular velocities (x^') of the hips, knees and ankles were measured and their phase angles obtained. The continuous relative phases (CRP) of the hip-knee and knee-ankle coordination were also calculated. The standard deviations of the CRP curve points were averaged to obtain deviation phase (DP) values for the stance and swing phases. The TCC group was found to cross obstacles with increased leading and trailing toe-clearances with unaltered CRP values when the swing toe was above the obstacle. Long-term TCC training altered the patterns and magnitudes of the CRPs primarily over double-limb support and significantly reduced the variabilities of leading knee-ankle and trailing hip-knee and knee-ankle CRP curves over the crossing cycle, regardless of obstacle height. The current results suggest that long-term TCC practice was helpful for a crossing strategy with significantly increased foot-obstacle clearances and reduced variability of the way the motions of the lower limb joints are coordinated during obstacle-crossing. These benefits may be explained by the long-lasting effects of continuous practice of the slow movement patterns emphasizing between-limb transfer of body weight in TCC.